The Development Pathway of the Aquatic Vegetable Industry Cluster in Baoying County, Jiangsu Province - Wu, Man (Journal of Global Economy, Business and Finance, 2025)
The development of agricultural industrial clusters is instrumental in addressing the challenges of product homogenization and uncoordinated regional competition, thereby fostering the competitive advantages of regional specialty industries. The aquatic vegetable industrial cluster in Baoying County, Jiangsu Province, serves as a representative and exemplary case. This paper aims to analyze the developmental stages and pathways of the Baoying cluster, offering valuable insights for the construction of other characteristic agricultural clusters. The findings indicate that the development of Baoying’s aquatic vegetable cluster has progressed through three distinct stages: (1) a phase of large-scale expansion and specialization; (2) the development of a processing sector leveraging local resource endowments; and (3) the establishment of a complete, whole-chain industry. Guided by market demand, Baoying County has adopted a multi-faceted development path characterized by the scaling of enterprises, standardization of products, diversification of business formats, establishment of win-win cooperation mechanisms, and a systematic policy framework. This strategic approach has propelled the cluster’s construction, with a primary focus on industrial chain extension and overall industrial upgrading.